Sujud Tilawa: Analysis of the Dalil in the Hadith and Fiqh - M Jakfar, Tarmizi; Binti Bakri, Siti Najwa (Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Sujud Tilawah is a prostration that is performed when someone reads and hears the sajdah verse either in prayer or outside prayer. The ulema agree about sujud tilawah in Islam but have different opinions regarding the law on sujud tilawah. According to Hanafis, sujud tilawah is obligatory while the jumhur ulama say it’s recommended. This difference of opinion arises because the scholars differ in using hadith as proof in establishing the law. In this research, the author uses a qualitative research method with the type of library research and this research uses a comparative descriptive approach, which the author compares the hadiths used by Islamic school scholars as evidence in interpreting the law of sujud tilawah. The results of the research show that in the hadith book (Kutubussittah) there are thirteen hadiths showing the Prophet and aṣ-ṣaḥāba performing sujud tilawah after hearing the recitation of the sajdah verse and four hadiths showing the Prophet and aṣ-ṣaḥāba abandoning the act of sujud tilawah after hearing the sajdah verse. Furthermore, to enforce the law of sujud tilawah, the Hanafi School uses one hadith narrated by Ibn Majah number 1052. The Maliki School uses one hadith narrated by Bukhari number 1077. The Syafi'i school uses three hadiths narrated by Abu Dawud number 1404 and Bukhari number 1077 and number 2678. The Hanbali school uses two hadiths narrated by Abu Dawud number 1404 and by Bukhari number 1077. The Dzahiri school uses one hadith narrated by Abu Dawud number 1404.